Bishop and chapter : the organisation of Irish medieval cathedrals, c.1111 - 1378 - Bates, Rhiannon Carey (Trinity College (Dublin, Ireland). Department of History, 2017)
This thesis explores the organisation of Irish cathedral chapters and places them within the wider European context of medieval cathedral studies. As the seat of the bishop, cathedrals were the focal point in every diocese and the most important churches outside of Rome. The objective is not to produce a history of the liturgical life of the cathedral, but rather a study of the cogs on which the machinery of the cathedral turned - its chapter. Therefore the aim of this thesis is to examine the morphology of Irish cathedral chapters from the Synod of Raith Bressail in 1111 to the dawn of the Great Western Schism in 1378
Keywords: Histories & Humanities, Ph.D.; Ph.D. Trinity College Dublin, 2017